Isolation and characterization of phosphate-solubilizing bacteria in land managed with the dusung system - Ohiwal, Morgan; Marasabessy, Rendy; Yunita, Melda; Sukmawati, Sukmawati; Qibtiyah, Mariyatul (JPBIO (Jurnal Pendidikan Biologi), 2025)
Soil microorganisms play a crucial role in nutrient cycling and soil fertility, particularly through their ability to solubilize insoluble phosphate compounds. This study aims to isolate and characterize phosphate-solubilizing bacteria (PSB) on land managed under the dusung agroforestry system. Soil samples were collected from five types of land use: forests, mixed orchards, clove hamlets, nutmeg orchards, and shrubs. PSB isolation was performed using Pikovskaya medium with the spread plate method, followed by characterization of colony morphology (shape, edge, color, elevation) and Gram staining. The results showed that the highest PSB population occurred in forest land (8.3 × 10? CFU/ml), followed by mixed orchards (6.2–6.7 × 10? CFU/ml), clove orchards (5.3–5.4 × 10? CFU/ml), nutmeg orchards (3.2–5.6 × 10? CFU/ml), and the lowest in shrubs (7.1 × 10³ CFU/ml). The characteristics of PSB varied, with isolates from forests and nutmeg orchards predominantly consisting of coccus-shaped Gram-positive bacteria, while those from mixed and clove orchards were dominated by bacillus-shaped Gram-positive bacteria. The population and diversity of PSBs were influenced by the availability of organic matter, soil pH, and land management practices. These findings highlight the ecological importance of the dusung system in sustaining soil fertility and promoting ecosystem resilience.